2021
DOI: 10.1007/s12208-021-00281-8
|View full text |Cite
|
Sign up to set email alerts
|

Managing charity 4.0 with Blockchain: a case study at the time of Covid-19

Abstract: The Covid-19 emergency is demonstrating the need to follow new solutions that can support the important role played by non-profit organizations around the world. Contrary to what should have happened to further combat the effect of pandemic, the majority of philanthropic organisations had a negative impact on fundraising, suffering a substantial decrease. Today, the Blockchain can play a pivotal role to re-establish pre-pandemic standards and enhance the development of global philanthropy. However, it is still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 68 publications
0
15
0
1
Order By: Relevance
“…The proposed system was build on top of the Ethereum network and can facilitates information sharing, allocate the funds as well as internal management. The authors in [102] presented a BC-based Charity 4.0 using the example of Charity Wall as a case study. The study presents the shortcoming of the platform and drawing comparisons to how BC technology help in preventing them.…”
Section: Paymentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed system was build on top of the Ethereum network and can facilitates information sharing, allocate the funds as well as internal management. The authors in [102] presented a BC-based Charity 4.0 using the example of Charity Wall as a case study. The study presents the shortcoming of the platform and drawing comparisons to how BC technology help in preventing them.…”
Section: Paymentsmentioning
confidence: 99%
“…They also have pointed out the urgent need for redesigning of the current structure of supply chains and include localization, agility and digitization. These can be [113] 2019 Proposed BC framework called Charity-Chain Build on the Ethereum network and provides the donor with complete knowledge of their donation Yaeger et al [134] 2019 Eliminate mistrust using smart contracts Fine is levied on the doctor if mistake is made Xuan et al [133] 2020 Incentive mechanism based on smart contracts Dynamically hand out rewards to encourage the volunteers Wu et al [129] 2020 End-To-End BC framework to manage charity contributions Information sharing, donation allocation, internal management Rangone et al [102] 2021 Proposed BC-based Charity 4.0 Case-study to point out advantages of BC achieved by integrating BC to the supply chain management system and thus create resilience, minimize waste, and support a more sustainable supply chain [83]. Patrick et al [115] suggested a drug supply chain management system based on BC technology which they called Pharmacosurveillance BC System.…”
Section: Supply Chain Managementmentioning
confidence: 99%
“…One of the promising areas of blockchain is the record-keeping of charity organizations' activities. A lot of attempts [8,[11][12][13][14][15][16][17][18][19][20][21] have been made to find a way for a proper charitable platform to run based on blockchain technology. Muhammad, Misbah and Adnan [12] claimed that the current systems are unstructured, vague, and lacking in donor confidence.…”
Section: Related Workmentioning
confidence: 99%
“…Rizal Mohd Nor et al [15] proposed a blockchain-based donation system to solve the issues of third-party extra fees, payment processing delays, and accountability. Adalberto Rangone and Luca Busolli [16] examined the idea of Charity Wall [17] and suggested that different aspects of blockchain technology can be used to strengthen the philanthropic system. Furthermore, Wang 'Jia and Chen Haifeng studied the blockchainbased charity application in China and acknowledged that many common issues related to donation systems can be avoided by using blockchain.…”
Section: Related Workmentioning
confidence: 99%
“…Most of the NPOs have taken a considerable hit across the board on fundraising (Rangone & Busolli, 2021). More specifically, despite the NPOs' efforts, it has been noticed a decrease in funding and reported difficulties in reaching donors (Kim & Han, 2020).…”
Section: Donating Intentionmentioning
confidence: 99%